Implementing the 2030 Bilingual Education Policy in Indonesian Private Schools: A Case Study of Santo Yoseph Catholic High School - Kresna Ningsih Manik (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Since the launch of the “Bilingual Policy for all schools supported by Yayasan Pendidikan Katolik (YPK) Don Bosco KAM in 2030,” schools have debated its impact. Teachers of non-English subject express concern about adapting, while parents fear their children may struggle with bilingual instruction. This study investigates how students, teachers, parents, and staff at Private Senior High School of Santo Yoseph Medan perceive the Bilingual education policy decided by YPK Don Bosco KAM in 2030. The research explores key concerns: the necessity of the policy, its effect on local languages, feasibility by 2030, budget sufficiency, availability of qualified teachers, and whether non-English subject teachers can teach bilingually. A questionnaire with seven questions was distributed to 40 participants in Indonesian and later translated into English. Results show 60% believe bilingual education is essential, 10% disagree, 25% are uncertain, and 5% have no opinion. While over half support the policy, challenges remain, including limited funding, a shortage of trained bilingual teachers, and the need for more English classes and learning materials. Successful implementation requires the Don Bosco Catholic Education Foundation to increase funding and address these challenges to ensure smooth integration of bilingual education by 2030.